PERTUMBUHAN DAN HASIL BAWANG MERAH LEMBAH PALU PADA BERBAGAI DOSIS PUPUK ORGANIK CAIR BIOKULTUR URIN SAPI - Sri Anjar Lasmini; Imam Wahyudi; Burhanuddin Nasir; Rosmini Rosmini (Universitas Tadulako, 2017)
Shallot growth is strongly influenced by climatic factors and available soil nutrients. By doing appropriate fertilization, the plants will get the nutrients needed. This study aimed to determine the effect of cow urine bioculture (liquid organic fertilizer) rates on shallot growth and yield. The research was conducted in Oloboju village, Sigi Biromaru sub district, Sigi Regency, Central Sulawesi Province from March to June 2017. The study used a randomized completely design which consisted of with no application of bioculture liquid fertilizer (B0), 250 L ha-1bioculture liquid (B1), 500 L ha-1bioculture liquid (B2) and 750 Lha-1bioculture liquid (B3). Each treatment was replicated four times, so there were 16 experimental units. Each unit of experiment consisted of 260 plants so that a total of 4160 plants were grown. The results showed that the bioculture liquid fertilizer applied at the rate of 750 L ha-1 resulted in significantly higher plant height, bulb diameter, bulb water content, number of tillers per hill, fresh weight of bulb, bulb bulk weight, dry weight of plant and bulb yield per hectare compared to the other treatments. Adding the bioculture liquid fertilizer at the rate of 750 L ha-1 produced shallot bulb of 9.27 ton ha-1.